Muscular echynococcosis.: a propósito de 2 casos - Mori, Raúl; López, Daniel; Schneeberger, Federico; Bentancur, Bernabé; Bado, Alejandro (Cirugía del Uruguay, 1987)
Two cases of muscular hydatic cysts are presented. The casuistic of the Hospital de Clínicas between 1972 and 1984 is reviewed. Sorne clinico-pathological consi• derations about this rare localization are done. Sorne diagnostic and therapeutic aspects are pointed out.